Features of the socialization of youth in the context of digital culture (Eurasian Journal of Research, Development and Innovation, 2024)
The scientific article attempts to explain the behavior of a person in the Internet space and the popularity of the Internet. Internet networks are considered not only as a source of information and a news resource, but as a powerful tool in the form of a separate digital environment with its own language, culture, values, and user behavior patterns. The main emphasis is placed on the fact that the Internet networks are an integral part of the socialization of the individual and can be qualified as a culture.